(untitled) (Research, Society and Development, 2022)
Despite of the development of technologies aimed at civil construction, one of the biggest obstacles to be overcome is the pathologies of buildings. This problem mainly affects the performance and lifespan of buildings, and occurs due to reduced deadlines, inadequate projects, inadequate use of materials, lack of maintenance, unskilled labor and lack of inspection. Therefore, this article analyzed a property composed of a precast concrete structure in the city of Bom Conselho-PE. The main objective of this work was to identify and characterize the main pathological manifestations in the structural elements of the construction. The methodology applied for the identification of pathologies consists of inspections, examinations, analyzes and interpretations. Furthermore, non-destructive tests were also used through sclerometry tests, with the objective of verifying the surface hardness of the concrete, providing elements for the evaluation of the quality of the hardened concrete and estimation of its compressive strength. The results made it possible to detect the existing problems, being possible to identify deformations in 81% of the beams, 33% of the columns with failures and 78% of the slabs with cracks. In this way, it was possible to establish the necessary technical guidelines for the repair and maintenance of the building.